The Complexities of Social Dining: Investigating Role of Impression Management, External Eating, and Known Companion Towards Food Portion - Pramudea Reza, Rere Deas; Undarwati, Anna (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2024)
This study aims to investigate how dining with acquaintances or friends, the desire to manage others’ impressions, and external cues such as smell and appearance, influence food portion sizes. The research employed a quasi-experimental design, involving 236 participants who were active students at Semarang State University, all of whom were not on a diet, did not have allergies, and non-vegetarians. A General Linear Model Univariate analysis reveals that individuals who ate alone had a bigger portion compared to when eating with a known companion (F(1,228)=4.059, p=0.045, partial η2=0.17). Furthermore, the impression management or external cues influenced the individuals to take bigger portions when eating alone (F(1,228)=5.290, p =0.022, partial η2=0.023; F(1,228)=4110, p=0.044). However, those with high impression management and external eating tendencies took larger portions when eating with a known companion (F(1,228)=4.652, p=0.032, partial η2=0.020). Thus, the presence of a known companion had a less significant influence on overall portion sizes (F(1,228)=4.059, p=0.045, partial η2=0.17). These findings suggest that known companions exert a complex effect on eating behaviors. Future research should provide clearer guidelines for the appropriate portion sizes companions should take, while emphasizing healthy food choices in social dining setting.